Penerapan Pembelajaran Toleransi Melalui Metode Bercerita Di Taman Kanak-Kanak Al-Qur’an Ruhama Takengon - sari, dewi purnama (Indonesian Journal of Islamic Early Childhood Education, 2018)
Planting tolerance education in kindergarten is still lacking, this is indicated by the child not listening to the teacher while speaking in front of the class, impatient in waiting for the queue, not sharing with friends, and lack of gratitude for the assistance given. The purpose of this study was to find out how the application of tolerance learning through the method of telling the impact of using the method of telling stories in the al-qur'an ruhama takengon kindergarten. This study uses a type of qualitative research with a descriptive approach. The results of the study show that the application of tolerance learning through the method of telling stories in al-qur'an kindergarten ruhama takengon, namely, the effort given by teachers to children to apply tolerance in daily life through habituation methods , as children accustom themselves to greeting others, patiently waiting for their turn, through the method of telling the teacher it will be easier to attract children's attention and easier to form good habits in the child.